Inspiring women: Experimental evidence on sharing entrepreneurial skills in Uganda - Patrick Lubega; Frances Nakakawa; Gaia Narciso; Carol Newman; Cissy Kityo (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2018)
This paper presents the results of a randomized control trial designed to test the impact of role models on the livelihoods of women living with HIV in Uganda. Participants in our treatment group were exposed to the screening of videos of role models telling their personal stories of the challenges and rewards of setting up a business. The role models intervention has a positive effect on the probability of starting a business, personal income and informal savings. The intervention improves the health of women and children and reduces the probability that children are absent from school.
Keywords: 330; Role models; RCT; HIV